The Impact of Decentralization in the Infrastructure Sector on Sustainable Development in the Municipality of Viqueque. - Costa Monteiro, Fretalino da; Muni, Joao (Green Publisher Indonesia, 2025)
This study explores the impact of Management Based on School (MBS) on improving the quality of education in rural Indonesia, focusing on the challenges and opportunities of implementing decentralization in education. Despite the potential benefits of MBS, such as increased school autonomy in managing curriculum and resources, rural schools face significant obstacles, including limited resources, inadequate teacher training, and low community participation. The purpose of this research is to assess how MBS influences educational quality in rural schools and to identify the key factors that support or hinder its successful implementation. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation from school principals, teachers, administrative staff, and community representatives. The results show that while MBS has led to improvements in school management and educational outcomes, challenges such as resource limitations and lack of support from local communities remain prevalent. In conclusion, the study highlights the importance of government support in training, funding, and community engagement to optimize MBS implementation. This research contributes to understanding the specific needs of rural schools in Indonesia and offers recommendations for enhancing MBS effectiveness in these contexts.